Genomic characterisation of Lacticaseibacillus paracasei phage ΦT25 and preliminary analysis of its derived endolysin. (May 2021) - Sunthornthummas, Sirinthorn; Doi, Katsumi; Fujino, Yasuhiro; Rangsiruji, Achariya; Sarawaneeyaruk, Siriruk; Insian, Kedvadee; Pringsulaka, Onanong
Abstract: Bacteriophage infection is a serious problem in milk fermentation where it causes a delay in the fermentation process and reduces product quality. This study provides the first molecular characterisation of a lactic acid bacteriophage from spoiled fermented milk tanks in the dairy industry in Thailand. Bacteriophage ΦT25 is virulent, and shows strong lytic activity against Lacticaseibacillus paracasei LPC. Genome analysis demonstrated that phage ΦT25 possesses a linear, double-stranded DNA genome of 38, 421 bp. To assay endolysin activity of phage ΦT25 (ORF35), Lysin vector pET21a was constructed by cloning the LysinT25 gene into plasmid pET21a. The size of LysinT25 endolysin was predicted to be ∼41 kDa LysinT25 was able to lyse a wide range of lactic acid bacteria and other Gram-positive bacteria, such as Staphylococcus aureus and Listeria monocytogenes . In addition, this endolysin has a synergistic inhibitory effect against Escherichia coli when combined with chloroform as an outer-membrane permeabiliser.